Expression and localization of tubulin isotypes and its mRNAs during Thecaphora frezii developments - Figueroa, Ana Cristina (2022)
Thecaphora frezii is a phytopathogenic fungus that infects Arachys hypogaea L. and produces peanut smut. It has three ontological stages teliospores, basidiospores, and hyphae. Microtubules are cellular structures that participate in various important cellular processes. In this work, we analyzed the presence and location of α-tubulin isotypes and enzymes that participate in tyrosination-detyrosination in the three stages of T. frezii. Although both tyrosinated and detyrosinated tubulin seem to be associated with a membrane fraction component that gives it a similar behavior to integral proteins, in the soluble cytosolic fraction, only detyrosinated tubulin was detected, not tyrosinated tubulin. The presence of α-tubulin was not detected using the monoclonal antibody DM1A as neither acetylated tubulin. The RNA-Seq analysis showed the presence of α, β, and γ-tubulins and the genes that codes for tyrosine-tubulin ligase and cytosolic carboxypeptidase 1, enzymes that are involved in post-translational modification processes. These sequences showed a high percentage of identity and homology with Ustilago maydis, Thecaphora thlaspeos, and Anthracocystis flocculosa. This is the first report for tubulins subpopulations and the cellular distribution in T. frezii, which together with the data obtained by RNA-Seq contribute to the knowledge of the pathogen, which will allow the development of control strategies